2014
DOI: 10.2147/jn.s49207
|View full text |Cite
|
Sign up to set email alerts
|

Rotenone-induced nigrostriatal toxicity is reduced by methylene blue

Abstract: This study investigated the effect of subcutaneously injected methylene blue on oxidative stress and nigrostriatal damage induced in the rat brain by systemic rotenone injection. Rotenone 1.5 mg/kg (injected subcutaneously three times per week) was given alone or in combination with methylene blue (5, 10, or 20 mg/kg subcutaneously daily) for 2 weeks. Brain concentrations of malondialdehyde, reduced glutathione, nitric oxide (nitrite), and acetylcholinesterase, paraoxonase 1 activity, and the antiapoptotic mar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 68 publications
3
12
0
1
Order By: Relevance
“…The transmitted signal is terminated by AChE in cholinergic neurotransmission. Study showed that pesticides including rotenone act as an AChE inhibitor and reduced the level of AChE enzyme which is in agreement with our study (Abdel-Salam et al, 2014;. In movement control DA acts as inhibitory neurotransmitter in basal ganglia and ACh acts as excitatory neurotransmitter.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The transmitted signal is terminated by AChE in cholinergic neurotransmission. Study showed that pesticides including rotenone act as an AChE inhibitor and reduced the level of AChE enzyme which is in agreement with our study (Abdel-Salam et al, 2014;. In movement control DA acts as inhibitory neurotransmitter in basal ganglia and ACh acts as excitatory neurotransmitter.…”
Section: Discussionsupporting
confidence: 92%
“…This decrease in AChE activity following rotenone administration was attenuated by curcumin treatment which may be linked to restoration of cholinergic activity resulting in observed normalized ACh levels. ACh plays an important role in motor control in the central nervous systems (Abdel-Salam et al, 2014). The transmitted signal is terminated by AChE in cholinergic neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Poteet et al (2012) showed that MB reduces the ROS production and provides neuroprotection in HT-22 cells against the rotenone toxicity. The subcutaneous infusion of MB reduced oxidative stress caused by repeated injections of the rotenone (Abdel-Salam et al, 2014). Some studies have found that the administration of MB significantly reduced mortality after cyanide poisons (Berling, 1970;Salaris et al, 1991;Sun et al, 2018, Wen et al, 2011, which inhibits IV complex of ETC.…”
Section: Discussionmentioning
confidence: 99%
“…The dye is also an effective remedy for encephalopathy caused by the alkylating agent ifosfamide [13,14]. Recent interest in MethyB focuses on its neuroprotective potential that has been demonstrated in various in vitro and in vivo models of Parkinson's disease [15][16][17], Huntington's disease ROS [18], and Alzheimer's disease [19], and in mitigating neurotoxicity caused by organophosphates [20]. It also protected against brain and liver damage during endotoxemia [21].…”
Section: Introductionmentioning
confidence: 99%